Kinetika Slow Release Pupuk Urea Berlapis Chitosan Termodifikasi - YC Danarto; Anggita Nugrahey; Sela Murni Noviani (Equilibrium Journal of Chemical Engineering, 2017)
During this time, the use of urea is not efficient, because about 40-70% of nitrogen in the fertilizer is not absorbed by plants. In order to increase the effectivity of nitrogen release in urea fertilizer, it needs to be coated with modified chitosan as slow releasing agent to form a hydrogel material by forming a cross linking with glutaraldehyde cross-linker.The aims of this research is to study the mechanism and the appropriate kinetic model of nitrogen release in slow releasing fertilizer of modified chitosan. This research was conducted by analyzing the ability of bio-hydrogel by calculating the percentage of swelling ratio and water retention of hydrogel and the nitrogen release in slow releasing fertilizer both in the soil and water. The experiments were conducted by varying the amount of urea used which  30 gram, 40 gram, 50 gram, 60 gram and 70 gram of urea fertilizer. The The release profile is then plotted on several models of diffusion kinetic such as zero order, first order, higuchi and korsmeyer peppas. The appropriate model of diffusion kinetic is chosen by the largest correction factor (R2).The results showed that nitrogen release of the slow releasing fertilizer in the soil with 50% urea content  and  the  water  followed  korsmeyer  peppas  model  with  fickian  mechanism. Nitrogen release in the soil with urea content of 30%, 40%, 60%, and 70% followed the korsmeyer peppas model with nonfickian mechanism.